ANALISIS PENGARUH IMPLEMENTASI PROGRAM KANG PISMAN TERHADAP EFEKTIVITAS PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DI KELURAHAN CICADAS - Kurniawati, Kurniawati; Saputra, Ginanjar Wira (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
This research is motivated by the waste emergency in Bandung City, which requires integrated handling through the Kang Pisman Program (Reduce, Separate, Utilize). Cicadas Village, as a densely populated area with limited land, faces specific challenges in implementing the policy. This study aims to analyze the magnitude of the influence of the Kang Pisman Program policy implementation on the effectiveness of waste reduction in Cicadas Village. The research method used is descriptive quantitative with simple linear regression analysis. Data were collected through a Likert-scale questionnaire distributed to resident respondents using simple random sampling. The results showed a coefficient of determination (R-Square) of 0.433, indicating that the Kang Pisman Program significantly influences waste reduction effectiveness by 43.3%, while the remaining 56.7% is influenced by other factors. The main constraints in the field include limited land for sorting facilities in narrow alleys and community discipline. The novelty of this research lies in the analysis of environmental policy effectiveness in urban residential areas with high demographic density. In conclusion, strengthening adaptive communal infrastructure and local cultural transformation are keys to optimizing future policies.